PENERAPAN PENDEKATAN SAVI DENGAN MENGINTEGRASIKAN AYAT-AYAT ALQURAN DITINJAU DARI MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA - Sri Sulasteri; Ulfiani Rahman; Sri Wahyuni; Andi Sriyanti (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Mathematics is one of the most important subjects, but it often becomes a scourge for most students. Lack of student motivation is an obstacle and also affects the learning outcomes in Mathematics. The SAVI (Somatic, Auditory, Visual, Intellectual) approach integrated with the verses of Al-Qur’an into mathematical material is an alternative method of learning. This article aims at describing students' motivation and learning outcomes in mathematics through that SAVI approach. The approach used is a quasi-experiment with non-equivalent control group design. The study was conducted at MTs Madani Alauddin Gowa. The sample consisted of class VIII A, 32 people as the control class and class VIII B, 32 people as the experiment class. Data were analyzed with descriptive and inferential statistical analysis. The results showed that the average students’ motivation increased 10% in the experimental class and in the control class increased by 3%; and the average student learning outcomes increased by 23% in the experimental class and in the control class increased by 7%. Thus, there are differences in learning motivation and student learning outcomes between classes that apply and those that do not apply the SAVI approach by integrating Qur'anic verses. In short, it effectively increases students' motivation and learning outcomes in mathematics so that it can become alternative learning methods.